The Effect of Animated Play Program on Irregular Posture Formation in Preschool Children - Laura Daniusevičiūtė Brazaitė; Brigita Grėbliauskienė (Lithuanian Sports University, 2019)
Background. Insufficient back muscle tone of 6-7-year-old children does not guarantee stable spin curves. The preschool children's posture is an important society problem that raises the scientists interest (Okely, Trost, Steele, Cliff, & Mickle, 2009), when posture is formed during the pre-school period and taking into account fine motor skills peculiarities, it is possible to ensure the optimal movement function (Rodger & Vishram, 2010). The purpose of this study was to identify the need for animated play programs and risk factors for the development of about 4-7-year-old children's abnormal posture. Methods. We analysed annual preventive health collaborating with public health professionals and pre-school medical personnel. Two social surveys were conducted using an anonymous online questionnaire for respondents. The first survey included questions to parents/caregivers (interpersonal level) in order to establish the psychomotor development of children up to one year of age and possible causes of abnormal posture formation. The second survey had questions to the kindergarten educators and administration (organizational level) in order to find out the need for animated play programs in the educational process. The survey questions were based on the child's motor development principles. Research participants were 311 parents/caregivers and 117 kindergarten educators. Anonymous online surveys were conducted between October and December of 2018. Results. According to the analysis of annual preventive health indicators, less than half of the pre-school age children were healthy in Kaunas city and with the age the number of healthy children decreased. Analysis of preventive health checks in pre-school children showed that skeletal muscle disorders were most common in children aged 4 to 6 years. Parents/caregivers, kindergarten educators and the administration indicated that physical activity had a positive effect on the child's posture in the educational institution, but parents/caregivers had doubts that kindergarten had a favourable environment for the child's posture correction. Conclusion. As a result, most kindergarten educators and administrators as well as parents/caregivers believed that animated play programs in kindergarten would help to improve posture.